Ctenocheloides almeidai sp. nov., a new ghost shrimp from Brazil (Decapoda, Ctenochelidae) - Anker, Arthur; Pachelle, Paulo P. G. (Zootaxa, 2013)
A second species of the ctenochelid genus Ctenocheloides Anker, 2010 is described based on a single female specimen collected on a rocky reef in front of Maceió, Alagoas, northeastern Brazil. Ctenocheloides almeidai sp. nov. represents the first record of Ctenocheloides in the Atlantic Ocean. The new species differs from C. attenboroughi Anker, 2010, the type species from Madagascar, in the number of teeth in the crista dentata of the third maxilliped, the proportions and ar-mature of the major and minor chelipeds, and several other characters. The microhabitats of C. almeidai sp. nov. and C. attenboroughi are remarkably similar: both species inhabit burrows made in rock crevices cemented by compact clay-like silt, at very shallow depths (1–1.5 m). A key to the western Atlantic species of the family Ctenochelidae is provided.